Web-Based Information System for the Disposition of Entry Letters in South Sumatra Province - Rapica Amalia, Rissa; Suyanto; Abdillah, Leon A.; Nasir, M. (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2024)
Technological developments in the government office environment are increasingly developing, as well as government agencies having to modernize administration, such as in the administrative section for managing incoming mail. There are many types of letters that enter agencies every day with different needs. These incoming letters are waiting to be followed up (dispositioned) by administrative leaders for further processing at the South Sumatra provincial Dispora service. Over a long period of time and a large number of incoming letters every day, conventional recording methods have become less effective and can cause losses to the service, including lost and scattered letters. In this research, the author aims to create a website-based information system for the disposition of incoming letters at the South Sumatra Province Dispora office. The method used is web engineering and building an information system using the recurring acronym programming language Hypertext Preprocessor (PHP), CodeIgniter Framework and MySQL as the database. This website was created to make it easier for the work of managing incoming mail at the South Sumatra Province Youth and Sports Office to run well and optimally, by creating a website to automate incoming mail into electronic mail in the South Sumatra Province Youth and Sports Office